Use of Twitter by a Public Library During the Pandemic - Rathi, Dinesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
<span data-sheets-value=""1":2,"2":"Social media such as Twitter and Facebook are used by organizations including public libraries to disseminate a variety of information to community members. This research aims to identify key areas in which Twitter was used to share information with users during the initial pandemic phase by a large public library operating in the Western region of Canada. The findings resulting from the analysis of 150 tweets revealed that the library shared information primarily in the following areas: Programs and Services, Library Operations, Health and Hygiene, Resources, and Other."" data-sheets-userformat=""2":8961,"3":"1":0,"11":0,"12":0,"16":12">Social media such as Twitter and Facebook are used by organizations including public libraries to disseminate a variety of information to community members. This research aims to identify key areas in which Twitter was used to share information with users during the initial pandemic phase by a large public library operating in the Western region of Canada. The findings resulting from the analysis of 150 tweets revealed that the library shared information primarily in the following areas: Programs and Services, Library Operations, Health and Hygiene, Resources, and Other.